A contribuição do esforço inovativo para o desempenho exportador : uma análise para países latino-americanos - Pella, Antônio Fernando Costa (2019)
This work aims to estimate the contribution of the innovative effort on the probability of export and the intensity of exports of manufacturing companies from selected Latin American countries, namely: Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Paraguay, Peru and Uruguay. We use as proxy the binary variable “introduction of new products in the market”. There are evidences in the empirical literature on the international economics that export success is positively related to ex-ante productivity gains. Based on this hypothesis, we use three econometric models of dichotomous response in cross-sectional data, the Probit; the bivariate Probit, to correct the endogeneity problem between the innovation and export binary variables by means of instrumental variables; and the Heckman’s sample selection model, which corrects the selection bias of the sample in the estimation of the intensity of exports. The microdata were collected on the database of the Enterprise Survey, a firm-level research linked to the World Bank. The results showed that the innovation coefficient is positive and statistically significant in seven of the ten countries and signaled that the innovative effort increases the probability of exporting, while the estimation of the intensity of exports did not find statistically significant results in most of the countries surveyed.